Research into the optimisation of spectral quality to improve plant growth and development towards LED lighting and closed loop control for horticulture - Eftekhar Khansari, Tiva (2019)
The Light Emitting Diode (LED) technology has made significant achievements in the last decade. The efficiency and light output of High-power LEDs has increased exponentially compared to miniature LEDs. There has been an increasing and evident trend for the use of these high-power LEDs in our daily life. The advantages of LED technology in terms of high-efficiency, low cost, programmability and long-lasting make them an attractive replacement for traditional grow light solutions. This research focuses on a new application of the use of high-power LEDs for illuminating and improving the growth of plants. This thesis describes the design, construction and test of LED lighting for the growth of plants. This research has successfully demonstrated two topics: (i) the replacement of conventional broad-waveband `white' lighting with narrow- waveband LED lighting, and (ii) a description of the need for the use of Photosynthetically Active Radiation (PAR) sensors to monitor the amount of light illuminating the plant using LEDs for optimisation of the spectral quality to improve plant growth and development.